2020
DOI: 10.1103/physrevlett.124.033401
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization and Sub-Poissonian Density Fluctuations in a Degenerate Molecular Fermi Gas

Abstract: We observe thermalization in the production of a degenerate Fermi gas of polar 40 K 87 Rb molecules. By measuring the atom-dimer elastic scattering cross section near the Feshbach resonance, we show that Feshbach molecules rapidly reach thermal equilibrium with both parent atomic species. Equilibrium is essentially maintained through coherent transfer to the ground state. Sub-Poissonian density fluctuations in Feshbach and ground-state molecules are measured, giving an independent characterization of degenerac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
25
1
Order By: Relevance
“…We also would like to point out that the density fluctuation measured in experiments (12,14), f(r s ) = 〈n 2 (r s )〉 − 〈n(r s )〉 2 , is different from the density-density correlation, S(r), studied in our work. Whereas S(r) directly tells us all contacts by capturing the probability of having two particles as a function of r, their relative coordinate, f(r s ) traces the compressibility ∂n/∂ as a function of r s , the single-particle coordinate.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…We also would like to point out that the density fluctuation measured in experiments (12,14), f(r s ) = 〈n 2 (r s )〉 − 〈n(r s )〉 2 , is different from the density-density correlation, S(r), studied in our work. Whereas S(r) directly tells us all contacts by capturing the probability of having two particles as a function of r, their relative coordinate, f(r s ) traces the compressibility ∂n/∂ as a function of r s , the single-particle coordinate.…”
Section: Discussioncontrasting
confidence: 55%
“…With decreasing the temperature, the suppression of the loss rate no longer agrees with the Bethe-Wigner threshold. Experimental results also indicated that the temperature dependence of the density fluctuation is similar to that of the loss rate (12,14). A theory fully incorporating quantum many-body effects is, therefore, desired to understand the chemical reaction rate at low temperatures.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This geometry allows us to take advantage of the anisotropic character of the dipolar potential and retain only the repulsive side-to-side dipole-dipole interactions within each 2D site, while preventing the attractive head-to-tail interactions that facilitate losses at short range. Our recent advances in the production of degenerate Fermi gases of polar molecules 7 , 8 , combined with precise electric field control using in-vacuum electrodes 32 ( Fig. 1 ), allow us to perform a systematic characterization of the properties of a 2D Fermi gas of polar molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Inelastic losses in molecular collisions 2 5 , however, have greatly hampered the engineering of low-entropy molecular systems 6 . So far, the only quantum degenerate gas of molecules has been created via association of two highly degenerate atomic gases 7 , 8 . Here, we use an external electric field along with optical lattice confinement to create a two-dimensional (2D) Fermi gas of spin-polarized potassium-rubidium (KRb) polar molecules, where elastic, tunable dipolar interactions dominate over all inelastic processes.…”
mentioning
confidence: 99%